2001
DOI: 10.2460/javma.2001.219.1216
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Salmonella serotypes in cull (market) dairy cows at slaughter

Abstract: 58 Salmonella serotypes were isolated from market dairy cows at slaughter and could pose a threat for food-borne illness. Salmonella Montevideo was the most frequently isolated serotype and may contribute substantially to salmonellosis in dairy cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Numerous studies have examined the prevalence of Salmonella on hides and carcasses of fed and cull cattle at slaughter (9,11,15,39,64). However, studies examining antimicrobialresistant-Salmonella prevalence and diversity in beef production settings are fewer (9,51,78).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have examined the prevalence of Salmonella on hides and carcasses of fed and cull cattle at slaughter (9,11,15,39,64). However, studies examining antimicrobialresistant-Salmonella prevalence and diversity in beef production settings are fewer (9,51,78).…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of MDR Salmonella serotypes isolated from hide samples was examined by calculating Simpson Simpson's index of diversity were made using a one-way ANOVA and Bonferroni's multiple-comparison posttest (39,67).…”
Section: Methodsmentioning
confidence: 99%
“…Montevideo, a serotype often isolated from dairy cattle with salmonellosis (Galland et al, 2001) and one of the top 20 most frequently reported serotypes in humans (CDC, 2004), was recovered from a pigeon and from all three types of environmental samples. Correspondence of serotypes found in humans, cattle and pigeons indicate that transmission is a concern, and pigeons represent a potential source of contamination to cattle and human health.…”
Section: Salmonellamentioning
confidence: 99%
“…N umerous studies have examined the prevalence with which Salmonella organisms can be isolated from the feces of dairy cattle 1,2 and the serotype distribution 3 and antimicrobial susceptibility patterns [4][5][6][7] of strains that have been isolated. Other studies 1,8,9 have examined farm-and herd-level risk factors associated with fecal shedding of Salmonella spp in dairy cattle.…”
mentioning
confidence: 99%